1979
DOI: 10.1021/j100479a001
|View full text |Cite
|
Sign up to set email alerts
|

Rate constant measurements for the reaction Cl + CH2O .fwdarw. HCl + CHO. Implications regarding the removal of stratospheric chlorine

Abstract: The flash photolysis resonance fluorescence technique was employed to investigate the rate constant for the reaction Cl + CH20 -»• HCI + CHO from 223 to 323 K. An Arrhenius fit of the data gives ki = (1.09 ± 0.40) X 10"10 exp[-(131 ± 98)/T] in units of cm3 molecule'1 s'1. The results are compared to two very recent kinetic studies and are assessed in view of the reaction's role in disrupting the Cl-CIO stratospheric ozone depletion chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…(23) C1+ CH20 -+ HC1+ HCO k23 = 4.22 X 10IOM-' sec-l at 296 K [9] Reaction (5) is one of the chain-propagating reactions, and in reaction (22) Hz works as radical trapping, since H combines 0 2 rapidly to form HOz in our experimental conditions, and HO2 does not work as a chain carrier.…”
Section: Chain Carriermentioning
confidence: 85%
“…(23) C1+ CH20 -+ HC1+ HCO k23 = 4.22 X 10IOM-' sec-l at 296 K [9] Reaction (5) is one of the chain-propagating reactions, and in reaction (22) Hz works as radical trapping, since H combines 0 2 rapidly to form HOz in our experimental conditions, and HO2 does not work as a chain carrier.…”
Section: Chain Carriermentioning
confidence: 85%
“…Despite increasing recognition of the importance of formaldehyde in both stratospheric and marine boundary layer chemistry, there have been no direct measurements of the rate coefficient for reaction (3) since 1981. The two most comprehensive studies 14,15 reported good agreement at room temperature, but disagreed about the temperature dependence of the rate coefficient. At lower stratospheric temperatures of $220 K, the two expressions differ by 25%.…”
Section: Rate Coefficients For CL Abstraction Reactionsmentioning
confidence: 97%
“…The room temperature kinetic measurements are all in good agreement but there is some uncertainty as to the temperature dependence of reaction (3). 14,15 The reaction of chlorine atoms with acetaldehyde…”
Section: Wwwrscorg/pccpmentioning
confidence: 99%
“…The reactions between halogens and CH 2 O have attracted attention as the hydrogen abstraction reaction of Br+CH 2 O is an important termination step in the Br‐dominated destruction of ozone in the Arctic troposphere, as well as being a major sink for CH 2 O in this area [15,16] . Kinetics and mechanisms have been reported for F, Cl, Br, and I atom reactions [17–22] . MP2 calculations have estimated the barrier heights of the hydrogen abstraction reactions to be in the region of 4.4 kJ mol −1 to 17.2 kJ mol −1 for the F, Cl, and Br reactions.…”
Section: Introductionmentioning
confidence: 99%